The mediating role of life satisfaction in the relationship between physical exercise and depressive symptoms among middle-aged and elderly individuals - Yang, Ting; Li, Xinxin; Wang, Xinyu; Zhou, Jingjie; Chen, Wei (Frontiers in Public Health, 2025)
ObjectiveTo investigate the mediating effect of life satisfaction between physical exercise behavior and depressive symptoms among middle-aged and elderly individuals, providing a reference for improving depressive conditions in this demographic group.MethodsData from 11,101 middle-aged and elderly individuals from the 2020 China Family Panel Studies (CFPS) were collected. STATA 17.0 was used for data cleaning, organization, and statistical analysis which includes univariate analysis, stepwise regression analysis, and mediation effect testing.ResultsAmong 11,101 individuals aged 45 years and above, 2,272 participated in physical exercise, accounting for 20.47%; 2,052 exhibited depressive symptoms, representing 18.48%. Physical exercise was positively correlated with life satisfaction and negatively correlated with depression. Depression scores also showed a negative correlation with life satisfaction. According to the results of the mediation effect study, life satisfaction accounted for 16.60% of the overall effect and had a mediating effect value of −0.099 on depression symptoms.ConclusionPhysical exercise and life satisfaction are factors influencing depressive symptoms, and life satisfaction acts as a partial mediator between physical exercise participation and depression among middle-aged and elderly adults.